Riboflavin, a Potent Neuroprotective Vitamin: Focus on Flavivirus and Alphavirus Proteases - Eberle, Raphael J.; Olivier, Danilo S.; Amaral, Marcos S.; Pacca, Carolina C.; Nogueira, Mauricio L.; Arni, Raghuvir K. [UNESP]; Willbold, Dieter; Coronado, Monika A. (MDPI, 2022)
Several neurotropic viruses are members of the flavivirus and alphavirus families. Infections caused by these viruses may cause long-term neurological sequelae in humans. The continuous emergence of infections caused by viruses around the world, such as the chikungunya virus (CHIKV) (Alphavirus genus), the zika virus (ZIKV) and the yellow fever virus (YFV) (both of the Flavivirus genus), warrants the development of new strategies to combat them. Our study demonstrates the inhibitory potential of the water-soluble vitamin riboflavin against NS2B/NS3pro of ZIKV and YFV and nsP2pro of CHIKV. Riboflavin presents a competitive inhibition mode with IC50 values in the medium µM range of 79.4 ± 5.0 µM for ZIKV NS2B/NS3pro and 45.7 ± 2.9 µM for YFV NS2B/NS3pro. Against CHIKV nsP2pro, the vitamin showed a very strong effect (93 ± 5.7 nM). The determined dissociation constants (KD) are significantly below the threshold value of 30 µM. The ligand binding increases the thermal stability between 4 °C and 8 °C. Unexpectedly, riboflavin showed inhibiting activity against another viral protein; the molecule was also able to inhibit the viral entry of CHIKV. Molecular dynamics simulations indicated great stability of riboflavin in the protease active site, which validates the repurposing of riboflavin as a promising molecule in drug development against the viruses presented here.
Keywords: alphavirus; competitive inhibitor; flavivirus; NS2B/NS3pro; nsP2pro; riboflavin